Multicenter study for CH-VAD as a fully magnetically levitated left ventricular assist device - Yifan Lu; Shuanglei Zhao; Jie Han; Qiang Lv; Xin Du; Zhengdong Hua; Keli Huang; Zhenwei Ge; Xiaoning Sun; Dan Zhu; Yongfeng Shao; Hongjia Zhang; et al. (iScience)
Summary: The CH-VAD is a fully magnetically levitated left ventricular assist device (LVAD) designed for optimized hemocompatibility. This study evaluates the clinical outcomes of 77 patients implanted with the CH-VAD across seven centers in China from June 2022 to June 2024. Patients had a mean age of 57.5 years, primarily classified as INTERMACS 2 or 3, with dilated and ischemic cardiomyopathy as the main causes of heart failure (HF). The study reported a 91.6% survival rate at both 6-month and 1-year follow-ups, aligning with international LVAD outcomes. Key adverse events were infrequent, including low rates of right HF, reoperation for bleeding, and driveline infection. Importantly, no pump thrombosis or device failures were noted. The results suggest that the CH-VAD is a reliable and effective long-term mechanical circulatory support option for end-stage HF patients in China, warranting further studies for long-term efficacy evaluation.